Applications of template A3 and value-stream mapping in process improvement: the case of building elevators installation - Vieira,Gino Flávio (2021)
abstract: This article explores the application of lean thinking concepts in the analysis and obtaining of significant process improvements in building elevators installations. Based on a pilot installation, planned to analyze the installation processes of an elevator manufacturer, the authors compared two similar elevator installations. In one of them, they applied various lean thinking concepts and tools, with particular emphasis on template A3 and value stream mapping (VSM). This pilot installation planning was also developed based on the recommendations for efficient project management, structured by the Project Management Institute (PMI). The application of the template A3 and the value stream mapping to the installation of one of the elevators resulted in increased productivity, reduced installation times, and increased final quality of the product installed.